2017
DOI: 10.1021/acs.jpcc.7b09882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doping with Shallow Donors on Radiative and Nonradiative Relaxation in Silicon Nanocrystals: Ab Initio Study

Abstract: Electronic structures of 1−2 nm in diameter hydrogen-passivated silicon nanocrystals and rates of the radiative interband transitions and Auger recombination were calculated on the basis of first-principles (DFT/TDDFT) methods for the nanocrystals doped with a single centrally located phosphorus or lithium atom. We have found a significant increase of the radiative recombination rates caused by the nanocrystals' doping at room temperature. For the Pdoped crystallites, this effect takes place at zero temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Usually, the Auger recombination is an efficient process that can "shunt" other photonassisted processes such as light emission or multiple exciton generation. For instance, in Si crystallites, the Auger rates can be sufficiently high, as the measurements [133,134] and calculations [106,[135][136][137][138] show. Therefore, suppression of the Auger process is an important practical problem.…”
Section: Auger Recombinationmentioning
confidence: 95%
See 2 more Smart Citations
“…Usually, the Auger recombination is an efficient process that can "shunt" other photonassisted processes such as light emission or multiple exciton generation. For instance, in Si crystallites, the Auger rates can be sufficiently high, as the measurements [133,134] and calculations [106,[135][136][137][138] show. Therefore, suppression of the Auger process is an important practical problem.…”
Section: Auger Recombinationmentioning
confidence: 95%
“…It was revealed that doping of Si nanocrystals with P or Li is (under certain conditions) capable of improving their emittance [84,87,89,118]. In particular, the performed calculations [87,99,106,107] show that doping with P or Li can essentially increase the radiative transition rates.…”
Section: Silicon Nanocrystalsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was revealed that doping of Si nanocrystals with P or Li is (under certain conditions) capable of improving their emittance 85,88,90,119 . In particular, the performed calculations 88,100,107,108 show that doping with P or Li can essentially increase the radiative transition rates.…”
Section: Silicon Nanocrystalsmentioning
confidence: 98%
“…Many methods have been proposed to increase their emissivity, such as doping with shallow impurities [84][85][86][87][88][89][90] , growth in different matrices 91,92 , plasma 93,94 , and colloidal solutions [95][96][97][98][99] . As a result, numerous theoretical predictions and experimental observations of enhanced PL intensity 84,85,88,89 , radiative recombination rates 90,[100][101][102][103][104][105][106][107][108] and quantum efficiency of photon generation 109 have been reported.…”
Section: Silicon Nanocrystalsmentioning
confidence: 99%